Kepemimpinan Kepala Sekolah Dan Kedisiplinan Guru Smpn Kota Surakarta - Rahayu, Sri; Sutama, Sutama; Narimo, Sabar (Manajemen Pendidikan, 2014)
The objective of research was to examine the contribution of 1) teacher professional competency, motivation, and perception on headmaster leadership simultaneously to teacher discipline, and 2) teacher perception on headmaster leadership to teacher discipline. This study was a qualitative research with survey method, while the technique used was path analysis, used to examine the size of contribution indicated by path coefficient in every path diagram. The population of research was the teachers of public junior high schools in Surakarta city consisting of 1179 persons. The sample consisted of 300 teachers, taken using multistage random sampling technique. The author employed two-tailed test at significance level of 0.05. The results of research were that 1) there was a significant contribution of teacher perception on headmaster leadership to teacher discipline with contribution of 77.1% simultaneously, and 2) there was a significant contribution of teacher perception on headmaster leadership to teacher discipline by 77.1% The research could explain the total variability of 77.1%. The contribution of 22.9% came from variables excluded from the focus of research.